Pengaruh Social Media Marketing dan Marketplace Marketing terhadap Minat Beli Produk Tree-X - Cynthia Komala Ardy; Romauli Nainggolan (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2021)
Recently technology develops very rapidly. At the first time community only knew about radio, television, and newspapers, but along with the time human need gets more complex especially in information and communication so that scientists create sophisticated technology that can simplify human life. With advance in information and communication technology, recently the world does not know boundary. The internet also develops to adapt human need, even community use it as a means of buying and selling online goods or service in which recently is called online market. Online shopping is new phenomenon in shopping world in Indonesia. People prefer online shopping rather than having to spend time and energy to visit store directly. Therefore, Tree-X company utilizes online marketing to support sale. Tree-X company runs in wooden gifts and merchandises. The purpose of this research is to find out the effect of social media marketing and marketplace marketing on buying interest on Tree-X products. The variables in this research consist of social media marketing (X1), marketplace marketing (X2), and buying interest (Y). Data collection through online questionnaire distribution with the total sample of 100 respondents. Sampling uses purposive sampling technique. Data process uses Microsoft Excel 2013 and SPSS 22 For Windows. This research uses quantitative method and multiple linear regression analysis. The results of this research are social media marketing affects positive on buying interest and marketplace marketing affect positive on buying interest. The correlation value between social media marketing and marketplace marketing variables on buying interest variable is 75% can be concluded there is close relationship between independent variable and dependent variable in this research. The results of t test are social media marketing affects significant on buying interest of Tree-X products, marketplace marketing affects significant on buying interest of Tree-X products. The results of F test are social media marketing and marketplace marketing simultaneously have significant effect on buying interest of Tree-X products. Keywords: social media marketing, marketplace marketing, buying interest